(untitled) (Quinto Sol, 2024)
The article reconstructs the initial life of Evita, the rock opera composed by Andrew Lloyd Webber and Tim Rice, which appeared as a double disc at the end of 1976, and was brought to the theater by Harold Prince since 1978. Focusing on the reception of the theatrical premiere by critics, the text also analyzes some of the musical formal and performative elements. It also looks at certain aspects of Evita early material life. The article reveals the negative evaluation of the opera among the specialized critics due to its ambiguous and even favorable vision regarding the government of "los Perón", together with underlining the highly positive assessment of its achievements as a theatrical and musical event. As a correlate of this and the analysis of the impact on critics of two significant scenes from the musical, the text argues that Evita contributed since the 1970s to the dissemination of a new international icon of the female leader of Peronism.